2020
DOI: 10.3390/ani10091544
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Window on Sardinian Native Horse Breeds through Uniparental Molecular Systems

Abstract: Sardinia, an island located to the west of Italy in the Mediterranean Sea, boasts three native horse breeds: Giara, Sarcidano, and Sardinian Anglo-Arab. Here, we have investigated for the first time three loci of the non-recombining region of the Y chromosome (NRY) in 34 stallions from these breeds and performed a phylogenetic analysis of the maternal relationships among 178 previously published mitochondrial control regions. We found that the current NRY diversity of Sardinian horse breeds is linked to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In particular, differently from the European and North American breeds [ 92 , 136 ], almost half of Chinese horses did not show a direct link between the SNP T/A and the deletion in np 10,594 for the HT3 [ 138 ]. The same low variability in the other modern European breeds was observed in three local breeds from Sardinia (Italy), each showing one distinctive haplotype (HT1, HT2 and HT3) frequency: 50% of HT1 in the Sarcidano breed, 75% of HT2 in the Giara breed and 58% of HT3 in the Sardinian Anglo-Arab breed [ 139 ]. These haplotype distributions highlight the replacement of autochthonous Y chromosomes with the import of stallions belonging to three paternal lines (ancestral line, Neapolitan/Oriental and Thoroughbred wave) for the improvement of native breeds.…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, differently from the European and North American breeds [ 92 , 136 ], almost half of Chinese horses did not show a direct link between the SNP T/A and the deletion in np 10,594 for the HT3 [ 138 ]. The same low variability in the other modern European breeds was observed in three local breeds from Sardinia (Italy), each showing one distinctive haplotype (HT1, HT2 and HT3) frequency: 50% of HT1 in the Sarcidano breed, 75% of HT2 in the Giara breed and 58% of HT3 in the Sardinian Anglo-Arab breed [ 139 ]. These haplotype distributions highlight the replacement of autochthonous Y chromosomes with the import of stallions belonging to three paternal lines (ancestral line, Neapolitan/Oriental and Thoroughbred wave) for the improvement of native breeds.…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 63%
“…The widespread presence of HT1 and HT2 is probably due to the Oriental wave, as Arabian horses carrying these MSY haplotypes were imported into Central European studs, while the frequency of HT3 in modern horses is attributable to the intensive use of English Thoroughbred in the improvement of other horse breeds. The SNPs and indels identifying the different haplotypes were further investigated in 42 breeds from different areas of Europe, Asia and America [ 136 ] and in 13 Chinese indigenous [ 138 ], 3 Sardinian [ 139 ] and 1 Kazach [ 140 ] horse breeds ( Figure 2 and Table S3 ).…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 99%
“…Sarcidano Horse frequently has supernumerary bilateral upper premolars, which have disappeared in modern horse breeds, placing this breed on an archaic model (similarly to the Przewalski’s Horse). Previous research confirmed the marginal impact of crossbreeding on the Sarcidano Horse mitochondrial gene pools and the lack of recent gene flow from outside [ 2 ], suggesting that this breed represents an important resource to be preserved, but also an important model to be studied.…”
Section: Introductionmentioning
confidence: 73%
“…Within some species, populations may be isolated from others, and they could not be subject to gene flow. In this scenario, genetic differences are accumulated over evolutionary time until members of a population living in an isolated region will display similar types of genetic markers ( [119,120], as examples).…”
Section: Identification Of Sample Geographical Originmentioning
confidence: 99%